2018
DOI: 10.1093/jas/skx004
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of inappetent sheep in a feedlot using radio-tracking technology1

Abstract: The feeding and drinking behaviours of sheep were monitored using RFID technology at a commercial pre-embarkation feedlot in Western Australia with the aim of characterizing feeding and drinking patterns of inappetent sheep that might allow them to be treated. Feeding and drinking behaviours of sheep were compared with their survival and change in body condition. Patterns of number of visits and the time spent at feed and water troughs were analyzed for a total of 8,206 sheep, representing four consignments th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…The average performance (mean ± SD) of the APMS units was 99.83% ± 0.05 % for sensitivity, 99.93% ± 0.05% for specificity, 99.67% ± 0.13% for precision, and 99.91% ± 0.05% for accuracy. The developed APMS in this study demonstrated a much-improved performance compared to other RFID systems applied in animal behavior research to date (Adrion et al, 2018;Barnes et al, 2018;Brown-Brandl et al, 2018;Li et al, 2017). First, with the customized antennas, attachment of the transponders, and load cell data correction, this system achieved very high performance indicators.…”
Section: Apms Performancementioning
confidence: 91%
See 1 more Smart Citation
“…The average performance (mean ± SD) of the APMS units was 99.83% ± 0.05 % for sensitivity, 99.93% ± 0.05% for specificity, 99.67% ± 0.13% for precision, and 99.91% ± 0.05% for accuracy. The developed APMS in this study demonstrated a much-improved performance compared to other RFID systems applied in animal behavior research to date (Adrion et al, 2018;Barnes et al, 2018;Brown-Brandl et al, 2018;Li et al, 2017). First, with the customized antennas, attachment of the transponders, and load cell data correction, this system achieved very high performance indicators.…”
Section: Apms Performancementioning
confidence: 91%
“…To date, RFID is one of the most popular technologies that has been used to identify individual animals. It has been applied in animal behavior research of pigs (Adrion et al, 2018;Brown-Brandl et al, 2018;Maselyne et al, 2014), chicken (Campbell et al, 2017;Li et al, 2017;Li et al, 2018), cattle (Brown-Brandl and Eigenberg, 2015;Menzies et al, 2018), and sheep (Barnes et al, 2018;Doughty et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The developed APMS in this study showed a much improved performance compared to other RFID systems applied in animal behavior research to date (Li et al, 2017, Adrion et al, 2017, Adrion et al, 2018, Barnes et al, 2018. First and foremost, with the customized antennas, attachment of the transponders, and load cell data correction (or even without the weigh-based correction), this system demonstrates a set of superior performance indicators.…”
Section: Discussionmentioning
confidence: 88%
“…To date, one of the most popular technologies for identifying individual animals is the RFID technology. It has been applied in animal behavior research of pigs (Adrion et al, 2018), poultry (Li et al, 2017), cattle (Adrion et al, 2017), and sheep (Barnes et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…A shorter-term measure of feeding was required for our protocol; consequently, the number of troughs, the amount of feed available and cleanliness of feed troughs were included. The reviewed protocols do not include an animal-based measure to quantify feed intake; therefore, we developed a measure described as Feed Behaviour Score, because feeding behaviour is particularly important as it is informative about the immediate level of hunger, social competition for feed [41], and appetitive response to climatic challenges [42][43][44]. The Welfare Quality ® protocol contains additional measures for water provision, including water availability and cleanliness.…”
Section: Good Feedingmentioning
confidence: 99%